KUALITAS PELAYANAN PUBLIK DALAM PENERAPAN SIMKAH (SISTEM INFORMASI MANAJEMEN NIKAH) DI KUA KECAMATAN CIPARAY KABUPATEN BANDUNG - Neng Yanti (Sekolah Tinggi Pariwisata Mataram, 2022)
Abstract Referring to the Observation Data which shows the quality of public services in the implementation of SIMKAH at KUA, Ciparay District, which is quite good. The purpose of this study was to determine the effectiveness of the application of simkah in improving the quality of public services in the religious affairs office of the Ciparay sub-district; explained that this simkah can help and facilitate online marriage services. To respond to this, the researchers conducted research at the KUA office in Ciparay District with the aim of knowing the role of implementing simkah in improving the quality of public services in terms of marriage. This research was conducted at the KUA Ciparay District with a qualitative approach and descriptive method. Collecting data in this study using study documentation and interviews. This study found that the application of online simkah in improving service quality went well. With marriage registration from 2018 to 2021 with details; at the beginning of 2018 to be exact from September there were 315 registrants; In 2019 there was an increase to 1556 registrants; In 2020 it decreased due to the pandemic and PPKM became 1341 registrants and in 2021 it increased again to 1521 registrants. This shows that the application of simkah can help in providing good, fast and precise service to the community.